Pengaruh Indeks DJIA, Harga Minyak Dunia, Tingkat Inflasi, dan Nilai Tukar Rupiah terhadap ISSI - Muhammad Baharudin Mahfudz; Nurhadi Nurhadi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
Indonesia is a country where the majority of the population is Muslim, so information about the Sharia Stock Index has an important role in understanding the dynamics of the capital market in Indonesia. This study aims to determine the simultaneous and partial influence of Dow Jones Industrial Average (DJIA), World Oil Price, Inflation Rate, and Rupiah Exchange Rate on Indonesia Sharia Stock Index (ISSI). This study uses secondary data in the form of a summary of monthly index reports obtained from financial websites. The population in this study is a time series data that amounts to 60 months and starts from January 2016 to December 2020 by determining samples using saturated samples. The data was analyzed using multiple linear regression analysis techniques. Hypothesis tested using F test and t test. The results showed that simultaneously (Test F) variable Dow Jones industrial Average (DJIA) (X1), World Oil Price (X2), Inflation Rate (X3), and Rupiah Exchange Rate (X4) had a significant effect on the Indonesia Sharia Stock Index (ISSI) on the Indonesia Stock Exchange (IDX). Partially (Test t) DJIA has a significant positive effect on ISSI. Rupiah exchange rate has a significant negative effect on ISSI. Meanwhile, The World Oil Price and Inflation Rate have an insignificant negative effect on ISSI.